An Analysis of Code Mixing in the MOVIE â€œFrom London to Baliâ€ - Asrifan, Andi; Abdullah, Harun; Muthmainnah, Muthmainnah; Patil, Atul (Institut Agama Islam Negeri (IAIN) Curup, 2021)
examined is the types and level code-mixing. In types and level code-mixing, researchers used the Suwito theory. As for the types of code-mixing, including inner code-mixing and outer code-mixing, while in code-mixing level consists of six words: word-level code-mixing, phrase-level code-mixing, clause level code, baster level code-mixing, repetition level code-mixing, and code-mixing level idioms. This research design used is qualitative research. Qualitative research, among others, is descriptive. The data is collected more in the form of words or pictures rather than numbers. The qualitative descriptive method is a method that researchers can use to analyze by doing fact-finding with the right interpretation. Qualitative research is closely associated with the context. Based on the results of the analysis from London to Bali, the data was obtained for types of code-mixing consisting of inner code-mixing 115 data, outer code-mixing 46 data, and level code-mixing consisting of word-level code-mixing 145 data, phrase level code-mixing 10 data, code-mixing clause level 4 Data, baster level code-mixing 1 data, repetition level code-mixing 3 data, idiom level code-mixing 0 data.Â